Common Infectious Diseases of Insects in Culture Diagnostic and Prophylactic Methods - Gouli, Vladimir; Gouli, Svetlana; Marcelino, Jose.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2011)
This handbook gives a comprehensive and copious illustrated description, with original art work, of the most common diseases in laboratory reared insect colonies, comprising Viruses (Baculoviridae, Reoviridae, Poxviridae, Iridoviridae); Bacteria (Bacillaceae, Pseudomonadaceae, Enterobacteriaceae); Rickettsia; Fungi and Microsporidia and Protozoa. Gregarine and Coccidian parasitoids are also depicted. Manuals for the diagnostic of insect diseases have been published in the 90$1 (Bs, however, these were intended for professional insect pathologists or for proficient training in invertebrate pathology, hence requiring some scientific background in insect pathology. Currently, most guides are web based, not comprehensive and solely addressing the most common diseases in a particular insect, or group of insects, reared in laboratory facilities. A comprehensive and proficient practical handbook for students and technicians working with insect reared colonies is lacking in the current literature.s
Preface -- Introduction -- Chapter 1. Principal group of infectious insect diseases -- 1.1.Viral diseases -- 1.2. Bacterial diseases -- 1.3 Rickettsial diseases -- 1.4. Fungal diseases -- 1.5. Diseases of protozoan origin -- 1.6. Mixed infections -- Chapter 2. Manifestation of infection diseases in insect cultures -- Chapter 3. Methods of practical diagnostic diseases -- 3.1.Preliminary diagnosis -- 3.2.Processing of pathological material for analyses -- 3.3.Microscopic examination of pathological material -- Chapter 4. Prophylactics of infectious diseases in insect cultures -- 4.1. Selection of animals for establishment of healthy laboratory colonies -- 4.2. Insect sanitation and therapy of disease -- 4.3. Sanitary measures in rearing facilities -- General references.
Keywords: Life sciences; Microbiology; Entomology; Life Sciences; Entomology; Applied Microbiology